EXPLORING LONG AND SHORT VOWELS SOUND IN ED SHEERAN'S SONG - Sri Mulyati (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Linguistics is a science study about the using of language and its provisions inside. Historically, linguistics comes from Latin language "lingua" which means "language", in English "language" and in French it is known as "Parole" which means "utterance".To make it easier in learning and mastering linguistics, linguistics is divided into several branches of science, namely: Morphology, Phonology, Syntax, Pragmatics, semiotics, and Semantics. Linguistics focuses on human language as communitaion tool and all its aspects within it as a universal unit.This study the writer only focuses on phonetic study  for  long and short vowels sound in an English song lyrick. Through understanding phonetic in English song lyrick. In phonetic study, long and short vowels sound pronounciation can affected the meaning of the words. So do In English song lyricks.The result of the analysis that English song lyrick chosen is dominted by long vowels sound; /ɑ:/, /i:/, /u:/, and /aɪ/.